Micro-crosslinked hyaluronic acid hydrogel ameliorates skin aging through NFIX-mediated collagen regeneration - Fan Peng; Jingyi Du; Dongshuang Wang; Siling Huang; Xiaoman Xu; Lei Ji; Shuang Yang; Ruoxi Liu; Ming Gao; Zongqian Zhang; Wenxiu Wang; Yang Su; et al. (Chemical Engineering Journal, 2026)

Photothermal Agents in Cancer Therapy: Applications and Development Prospects - Shiyu He; Shuaipeng Feng; Yiming Han; Qingqing Xu; Jiaru Lan; Donghua Di; Da Wang; Siling Wang; Huan Zhai; Qinfu Zhao (Chemical Engineering Journal, 2026)

Rapid oxidation of benzo[a]pyrene by a magnetic field-enhanced ozone system: Ozone dissolution-mass transfer efficiency and generation of reactive species mechanisms - Siling Wang; Hui Wang; Nan Lv; Yanrong Ma; Ben Wang; Bin Dong; Zuxin Xu (Journal of Environmental Sciences, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Sex-specific effects of 6PPD on adult zebrafish: male-selective feeding inhibition, nutrient malabsorption, intestinal epithelial damage, and absence of reproductive toxicity - Yuanhua Wang; Jie Ren; Siling Zhang; Hao Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Revealing the significance of melatonin in postharvest quality of tomato fruit, especially in sugar metabolism and transport - Yunzhi Liu; Yiping Feng; Siling Chen; Yuna Pan; Junrong Xu; Wenjin Yu; Changxia Li (Postharvest Biology and Technology, 2026)

A copper-doped mesoporous nanoplatform with dual enzyme-mimic activities for amplified cuproptosis and immune response - Qingqing Xu; Shuaipeng Feng; Yue Cao; Yang Li; Zhu Liu; Qiuling Deng; Jiaru Lan; Donghua Di; Yuling Mao; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Ginger exosome-covered mesoporous polydopamine nanoplatform ameliorates liver fibrosis via antioxidation and macrophage phenotypic transformation - Junhong Zhou; Hongwei Xu; Zhu Liu; Yuling Mao; Yian Li; Liwan He; Shuaipeng Feng; Donghua Di; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Single-cell resolution reveals the cell types and transcriptomic landscape of the ovary in mandarin fish (Siniperca chuatsi) - Siling Zhang; Jie Ren; Shanwen Jiang; Xiaomin Miao; Yixi Tao; Ronghua Wu; Yun Li; Hao Xu (Aquaculture, 2025)

Innovative spherical Fe-Mn layered double hydroxides (LDH) for the degradation of sulfisoxazole through activated periodate: Efficacy and mechanistic insights - Junle Jian; Siling Zhang; Ping Chen; Dezhu Liu; Yishun Wang; Linsheng Liu; Zhenjun Xiao; Zihong Xu; Yuhang Pan; Wenying Lv; Guoguang Liu (Environmental Pollution, 2025)

Lipidomics and transcriptomics analysis revealed the role of the spleen of Nile tilapia (Oreochromis niloticus) in lipid metabolism - Yixi Tao; Yanling Chen; Jie Ren; Shanwen Jiang; Siling Zhang; Hao Xu; Yun Li (Aquaculture, 2024)

Enhanced degradation of sulfonamides by copper and cuprous oxides activated ferrate (VI) synergistically: Mechanism and applicability - Linsheng Liu; Yishun Wang; Yudan Zhang; Ping Chen; Dezhu Liu; Mengyang Niu; Junle Jian; Zihong Xu; Siling Zhang; Wenying Lv; Guoguang Liu (Journal of Environmental Chemical Engineering, 2024)

Metabolomics analysis of splenectomy of Nile tilapia (Oreochromis niloticus) reveals the spleen involved in regulating liver lipids and amino acids metabolism - Yixi Tao; Chunying Du; Shanwen Jiang; Siling Zhang; Jingyun Feng; Xiaomin Miao; Hao Xu; Yun Li (Frontiers in Marine Science, 2024)
The liver is essential for nutritional balance in fish, and liver damage in farmed fish often arises from factors like overfeeding, causing various health issues. Clinical observations indicate that liver diseases frequently involve spleen dysfunction, and there is evidence to suggest that the spleen has a significant impact on liver function. However, there has been no discussion on the role of the spleen in maintaining liver health in fish. To understand the role of fish spleen in liver metabolism, this study selected Nile tilapia ( Oreochromis niloticus ) as the experimental material and first established a tilapia splenectomy model. Various biochemical parameters of the liver and serum were measured, and the liver metabolism characteristics of the splenectomy group (SP group) and the sham operation group (SO group) were analyzed using metabolomics. After splenectomy, biochemical parameters of the liver and serum showed abnormalities, including significant increases in total cholesterol (T-CHO) and serum total bile acid (TBA) levels, alongside a significant decrease in liver TBA levels, suggesting impaired metabolic function and cholesterol deposition in the liver. Metabolomics analysis showed that metabolites such as lipids, lipid-like molecules, and organic acids and derivatives were differentially regulated between the SO and SP group. KEGG analysis showed that differential metabolites were enriched in lipid metabolism and amino acid metabolism. The metabolic pathway analysis of differential metabolites showed that after splenectomy, the low-activity urea cycle in the liver may accelerate lipid synthesis, while low concentrations of aromatic amino acids and taurine may inhibit lipid catabolism. These results indicate that after splenectomy, the liver metabolic capacity is impaired, which causes abnormal lipid metabolism by interfering with amino acid metabolism, making splenectomy tilapia liver at risk of liver disease, including cholesterol deposition, hepatic steatosis and nonalcoholic fatty liver disease (NAFLD). Our results show that the spleen is involved in regulating liver lipid and amino acid metabolism, and the spleen may interfere with lipid metabolism by regulating liver amino acid metabolism. Our data can provide support for further research on liver and spleen functions and the immune-nutrient metabolism mechanisms in fish, as well as new ideas for healthy fish farming.